Associação entre transtornos depressivos e saúde bucal: uma revisão sistemática de estudos observacionais - Kloeckner, Fernando Lopes (2024)
Background: to investigate the association between depression and oral health outcomes, such as periodontitis, gingivitis, dental caries, tooth loss and edentulism. Methods: a systematic search was conducted across seven major databases and two gray literature sources. Only studies with probabilistic samples, clinical assessment of oral outcomes, validated tools for measuring depression, and statistically controlled analyses for confounders were included. Study selection, data extraction, risk of bias and certainty of evidence assessment were independently performed by two reviewers. Results: 5,107 unique records were identified. Forty-five articles were included (37 cross-sectional, 8 longitudinal). Risk of bias was low for 39 studies. Depression was associated with periodontitis (OR=1.30, 95%CI 1.07-1.57, I2=56%), dental caries (PR=1.18, 95%CI 1.05-1.31, I2=41%) and edentulism (OR=1.26, 95%CI 1.16-1.37, I2=35%). Individuals with tooth loss (OR=1.24, 95%CI 1.03-1.51, I2=0%) and edentulism (OR=1.37, 95%CI 1.15-1.64, I2=69%) had a higher odd of depression when compared to their respective controls. Certainty of evidence was graded low for the metaanalyses. Limitations: Meta-analysis had a small pool of studies, precluding publication bias assessment. Most studies were cross-sectional, susceptible to biases such as reverse causality and residual confounding despite statistical adjustment. High heterogeneity was observed in outcome definitions, hindering comparisons between studies. Conclusion: Depression is associated with poor oral health with low certainty of evidence.